Volatile organic compounds of possible microbial origin and their risks on childhood asthma and allergies within damp homes. (January 2017) - Choi, Hyunok; Schmidbauer, Norbert; Bornehag, Carl-Gustaf
Abstract: Background: Risk of indoor exposure to volatile organic compounds of purported microbial origin on childhood symptoms of wheezing, rhinitis, and/or eczema, and doctor-diagnosed asthma, rhinitis, and eczema, respectively, remain unclear. Objective: To test hypotheses that total sum of 28 microbial volatile organic compounds (Σ26 MVOCs): 1) poses independent risk on doctor-diagnosed asthma, rhinitis, and eczema, respectively, as well as multiple symptom presentation with a minimum of the two of the above conditions (i.e. case); 2) is associated with significant interaction with absolute humidity (AH) on additive scale. Methods: In a case-control investigation, 198 cases and 202 controls were examined during November 2001 – March 2002 period through home indoor air sampling, air quality inspection, and health outcome ascertainment. Results: Not only the Σ28 MVOCs but also the global MVOC index were significantly higher within the homes of the cases with a high AH, compared to the controls with a low AH (all Ps < 0.001). Only the cases, but not the controls, were associated with a dose-dependent increase in the exposure variables of interest (Σ28 MVOCs) per quartile increase in AH (P < 0.0001 for the cases; P = 0.780 for the controls). Only among the children who live in a high AH homes, a natural log (ln)-unit of Σ 28 MVOCs was associated with 2.5-times greater odds of the case status (95% CI, 1.0–6.2; P = 0.046), compared to 0.7-times the odds (95% CI, 0.4–1.0; P = 0.074) of the same outcome among the low AH homes. Specifically, joint exposure to a high MVOCs and high AH was associated with 2.6-times greater odds of the doctor-diagnosed asthma status (95% CI, 0.7–8.91; P = 0.137). Conclusion: Joint occurrence of high Σ28 MVOCs and AH was associated with a significant increase in the case status and asthma risks in an additive scale. Highlights: Joint occurrence of Σ28 MVOCs and absolute humidity was associated with an indication of significant interaction in additive scale on multiple allergy symptoms and asthma diagnosis. The homes with a high concentration of the purported Σ28 MVOC were not only associated with a high absolute humidity, but also were poorly ventilated. Focused strategies to remediate indoor absolute humidity and ventilation are warranted for the protection of children from allergies and asthma.